A self-crosslinking monomer, α-pinene methacrylate: understanding and exploiting hydrogen abstraction. Issue 39 (5th September 2022) - Monaghan, Olivia R.; Skowron, Stephen T.; Moore, Jonathan C.; Pin-Nó, María; Kortsen, Kristoffer; Atkinson, Rachel L.; Krumins, Eduards; Lentz, Joachim C.; Machado, Fabricio; Onat, Zeynep; Brookfield, Adam; Collison, David; et al.
Abstract : A combined computational/experimental approach has been applied to investigate the self-crosslinking of α-pinene methacrylate via chain transfer through hydrogen abstraction. Abstract : Crosslinking is a valuable route to creating new polymeric materials and normally involves introduction of a cross linker or some form of secondary processing. Here we report the discovery and analysis of a self-crosslinking sustainable terpene derived monomer, α-pinene methacrylate (αPMA). This monomer undergoes crosslinking during free radical homopolymerisation and with comonomers e.g. methyl methacrylate (MMA). αPMA does not appear to contain any obvious functionality that would induce crosslinking such as vinyl bonds, but we postulate that it may undergo a fortuitous abstraction of a hydrogen atom from the pendant group. A combined computational (DFT) and experimental approach has been applied to investigate this. Further, we used DFT analysis to predict the behaviour of a related monomer, beta-pinene methacrylate (βPMA). To the best of our knowledge this is the first-time that self-crosslinking has been observed in free radical polymerisation of methacrylates via chain transfer through hydrogen abstraction from a pendant group. We have exploited this crosslinking to generate new, renewable poly high internal phase emulsions (polyHIPEs) that could rival those derived from fossil-based styrene- polyHIPEs and we have done this in a process which does not require any additional cross-linking agent.